1985
DOI: 10.3109/00313028509063739
|View full text |Cite
|
Sign up to set email alerts
|

Sialadenoma papilliferum

Abstract: Sialadenoma papilliferum is a rare benign papillary intraoral tumour most frequently affecting men over the age of 50. The tumour bears many similarities to adenolymphoma of the parotid and may be considered a variant of the latter. A case is presented and the literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The prognosis of SP is generally good compared to that of other oral epithelial malignant tumors. SP should be considered a differential diagnosis if the papillary tumor occurs in the oral cavity 1–3 . While the histopathological findings of SP are well‐documented, cytological analysis results are currently lacking 1,3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of SP is generally good compared to that of other oral epithelial malignant tumors. SP should be considered a differential diagnosis if the papillary tumor occurs in the oral cavity 1–3 . While the histopathological findings of SP are well‐documented, cytological analysis results are currently lacking 1,3 .…”
Section: Discussionmentioning
confidence: 99%
“…SP primarily occurs in minor salivary glands of the oral cavity. Its exophytic growth can result in the clinical misdiagnosis of other squamous epithelial tumors such as squamous cell papilloma (SCP) 2 . Recent advances in molecular investigations have found that SP is associated with a characteristic genetic alteration ( BRAF V600E point mutation or HRAS mutation) 3 …”
Section: Introductionmentioning
confidence: 99%
“…We included the case reported as "intraductal papilloma' by Castigliano and Gold (1954) 15 years before Abrams and Finck (1969) defined the term SP. We have not accepted the case reported by Grushka et al (1984) because it lacked surface exophytic growth: nor have we included the case reported by Chan et al (1985) because it was described clinically as a nodule and the micrographs do not indicate the exophytic papillary features of SP. There are serious doubts about the diagnosis of the palatal lesion reported by Solomon et al (1978) i.e.…”
Section: Discussionmentioning
confidence: 99%